Inclusión, tecnología y educación superior de la población con discapacidad visual - Reyes Domínguez, Patricia Magaly (2016)
Contemporary world, a territory where visuality has reached gigantic levels, education daily faces new challenges. One of the most important is the recognition of new scenarios for inclusion in degree education, specifically aimed at blind people; focus of this investigation, whose main objective is to approximate a possible answer to the following question: In the city of Quito, which universities have implemented an internal policy of inclusion for students with visual impairment? Resolve the question involves the assessment of the inclusion process that allows the completion of degree education, for people with visual disability; right guaranteed in the Constitution of the Republic of Ecuador and typified in the Law on Disabilities. The study was conducted within the Tiflo libraries of the following institutions: Polytechnic Salesian University (UPS), the University of the Armed Forces (ESPE) and the Latin American Faculty of Social Sciences (FLACSO). In summary, one can say that technological Tiflo space of the Salesian Polytechnic University is the busiest for blind users of the capital city; appearance claiming their predicaments on an inclusive and transformative education.